Atrakcyjność inwestowania w dobra rzeczowe na przykładzie nieruchomości i dzieł sztuki - Szalewska, Hanna; Piechaczek, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents the attractiveness of investing in material goods including real estate properties and works of art. It shows the specificity as well as potential benefits and risks of this kind of capital investment. The analysis leads to a conclusion that investing in material goods can be an interesting supplement and in some cases even an alternative for financial investments. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 415-423